2019
DOI: 10.1051/e3sconf/20198902008
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring gas hydrate formation with magnetic resonance imaging in a metallic core holder

Abstract: Methane hydrate deposits world-wide are promising sources of natural gas. Magnetic Resonance Imaging (MRI) has proven useful in previous studies of hydrate formation. In the present work, methane hydrate formation in a water saturated sand pack was investigated employing an MRI-compatible metallic core holder at low magnetic field with a suite of advanced MRI methods developed at the UNB MRI Centre. The new MRI methods are intended to permit observation and quantification of residual fluids in the pore space as h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Therefore, water content will be detected precisely and displayed directly in the saturation profile by proton NMR. The DHK SPRITE method was employed to measure the one-dimensional profiles [30], as shown in Figure 4. Water content obtained at different positions of samples are presented in Figure 4.…”
Section: Measurement Of Saturation Profilementioning
confidence: 99%
“…Therefore, water content will be detected precisely and displayed directly in the saturation profile by proton NMR. The DHK SPRITE method was employed to measure the one-dimensional profiles [30], as shown in Figure 4. Water content obtained at different positions of samples are presented in Figure 4.…”
Section: Measurement Of Saturation Profilementioning
confidence: 99%
“…The changes of liquid in the pores during the hydrate phase transition can be monitored by MRI technology, which can more intuitively observe the hydrate formation process. Shakerian et al [6] used MRI technology to study the formation process of gas hydrate in metal core holders and studied the formation rate of hydrate through the change of T 1 and T 2 relaxation time. Zhang et al [7] visualized the change of water saturation during the phase transition of methane hydrate through low-field nuclear magnetic resonance experiments and found that the spatial distribution of gas-water-hydrate during the phase transition of hydrate was not uniform over time.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of great significance to study the characteristics of MH formation and reformation. At the same time, there are many studies shown that MRI technique is a powerful analytical tool for noninvasive multidimensional quantitative analysis of flow and transport in porous media, such as the hydrate [3,4]. It provides a lot of technical support on fluid characteristics and hydrate research in recent years [5].…”
Section: Introductionmentioning
confidence: 99%